2015
DOI: 10.1038/aps.2015.14
|View full text |Cite
|
Sign up to set email alerts
|

Intratumoral estrogen sulfotransferase induction contributes to the anti-breast cancer effects of the dithiocarbamate derivative TM208

Abstract: Aim: Sulfotransferase-catalyzed sulfation is the most important pathway for inactivating estrogens. Thus, activation of estrogen sulfotransferase (EST) may be an alternative approach for the treatment of estrogen-dependent breast cancer. In this study we investigated the involvement of EST in anti-breast cancer effects of the dithiocarbamate derivative TM208 in vitro and in vivo. Methods: The viability of human breast cancer MCF-7 cells was determined using a SBB assay. Nude mice bearing MCF-7 cells were orall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
(76 reference statements)
0
19
0
Order By: Relevance
“…Oxidative regulation of E2 function via SULT1E1 modification (at Cys83) is reported [23]. One recent article extensively analyze that not only SULT1E1 but also a large number of E2 metabolizing proteins including sulfatases (STs), formyl glycine forming enzymes are redox regulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative regulation of E2 function via SULT1E1 modification (at Cys83) is reported [23]. One recent article extensively analyze that not only SULT1E1 but also a large number of E2 metabolizing proteins including sulfatases (STs), formyl glycine forming enzymes are redox regulated.…”
Section: Discussionmentioning
confidence: 99%
“…This is important that the level of SULT1E1 expression is inversely correlated with malignancy in breast cancers [22]. Induction of intra-tumoral SULT1E1 and reduction of estrogen concentration by TM208 contributes to the anti-breast cancer action [23].…”
mentioning
confidence: 99%
“…The cytosol of the harvested tumors in each group of the metastatic xenograft nude mice was prepared as previously described [21] . The concentrations of the metastasis-associated biomarkers MMP-2, MMP-9, E-cadherin, N-cadherin and clau-din1 were measured using commercial ELISA kits according to the manufacturer's instructions.…”
Section: Expression Of Metastasis-associated Biomarkersmentioning
confidence: 99%
“…This is important that the level of SULT1E1 expression is inversely correlated with malignancy in breast cancers [16]. Induction of intra-tumoural SULT1E1and reduction of estrogen concentration by TM208 contributes to the anti-breast cancer action [17]. Earlier studies suggested a potential oxidative inhibition mechanism for human SULT1E1 through Cys83 redox modification.…”
mentioning
confidence: 99%